Expert opinions in company sales forecasting - Dittmann, Paweł (Opinie ekspertów w prognozowaniu sprzedaży w przedsiębiorstwie, 2011)
Company sales forecasts are an essential aspect of company management. The forecasts may be construed using a variety of formal and non-formal models. The paper addresses the need of including expert opinion on each of the consecutive stages of the process, for forecasts employing the1st and the 2nd degree formal models.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 214-221
Keywords: prognozowanie; zarządzanie przedsiębiorstwem; forecasting; enterprise management; sales forecasting